WORK MOTIVATION OF PT BUMI DEVELOPMENT PERTIWI MADIUN EMPLOYEES: WORK MOTIVATION OF PT BUMI DEVELOPMENT PERTIWI MADIUN EMPLOYEES - Septianasari, Erlita Yuli; Ina Syarifah; Hastuti, Farida Tri; Syafitri, Eva Mirza (Politeknik Negeri Madiun, 2023)
Motivation is an impulse that can move a person to carry out any activity, whether originating from himself or from outside, in order to achieve the goals that have been set. This research aims to describe the work motivation of PT Bumi Pembangunan Pertiwi Madiun employees. The method used in this research is quantitative descriptive; this method explains the situation to be researched with the support of a literature study so that it further strengthens the researcher's analysis in making a conclusion. The population in this study were all employees at PT Bumi Pembangunan Pertiwi, with a sample size of 86 respondents. The data processing technique uses Microsoft Excel and SPSS 25. The indicators used in the motivation variable are physical needs, safety and health needs, social needs, esteem needs, and self-actualization needs. The results obtained show that employee work motivation is categorized at a medium level with a percentage of 73%. The order of application of employee motivation at PT Bumi Pembangunan after conducting research is safety and health needs, self-actualization needs, social needs, physical needs, and finally the need for appreciation. The need for appreciation for PT Bumi Pembangunan employees needs to receive attention from management. This is necessary to maintain and appreciate the work efforts of employees within the company so as to encourage employee morale.